A dermatoglyphic study in oral submucous fibrosis patients - Satish Kumar; Srinivas Kandakurti; Vasu Siddhartha Saxena; Arti Saluja Sachdev; Jyoti Gupta (Wolters Kluwer Medknow Publications, 2014)
Aims and Objectives: (1) To determine the fingerprint patterns in gutkha chewers with oral submucous fibrosis (OSMF) and in healthy controls without gutkha chewing habit and OSMF. (2) To observe and compare the variations of fingerprints in both these groups. Materials and Methods: A prospective study was conducted in the Department of Oral Medicine and Radiology, Career Postgraduate Institute of Dental Sciences and Hospital, Lucknow, with 50 subjects divided into two groups: group A consisted of 25 clinically and histologically proven OSMF cases and group B consisted of 25 controls without gutkha chewing habit and OSMF. Fingerprints were taken using the ink method described by Cummins and Midlo. Statistical analysis was done using Chi-square and Fisher's exact tests. Results: There was a marked decrease of tented arches, ulnar and radial loops, and an increase of simple whorls in OSMF subjects in comparison with normal individuals. Conclusion: Fingerprint pattern is genetically determined. Similarly, the tendency of development of OSMF in gutkha chewers is also genetically determined. An effort was made to compare the fingerprint patterns among gutkha chewers with OSMF in a small sample, which showed that there was a significant decrease of tented arches, ulnar and radial loops, and an increase of simple whorls in OSMF patients in comparison with normal individuals.